Technology Growth in Shipping Industry: An Overview - Donepudi, Praveen Kumar (American Journal of Trade and Policy, 2014)
Being the backbone of the world economy, the shipping industry impacts the lives of many people directly and indirectly. It needs continuous innovation and the adoption of new thought processes to handle the ever-growing demands of materials and goods around the world. It faces several challenges such as compliance with the environmental regulations and laws, changes in the global business models, the complexity of operations and management, risks and hazards to the people and the assets, and the cost of adopting new changes. This study highlights the benefits of greater collaboration with partners, more automation of manual processes, and higher productivity and capacity to handle future loads.
Keywords: Technology Growth; Shipping Industry; Manual Processes; Automation